Experimental study on the micro-mechanism and compressive strength of concrete with calcined coal gangue coarse aggregate - Shengpeng Hao; Wenyu Xu; Bambesiwe M. May; Zhenyu Zhang; Yuyu Zhang (Case Studies in Construction Materials)
Coal gangue, a byproduct of coal beneficiation, has low strength and high carbon content, which negatively affects the mechanical properties of concrete when used as a substrate for natural gravel. However, high temperature calcination can activate its pozzolanic properties, improving its suitability for concrete production. This study investigates the microstructural and mechanical property of concrete incorporated with calcined coal gangue coarse aggregate at different temperatures (500°C, 600°C, 700°C, and 800°C). The experimental results indicate that metakaolin in coal gangue begins to decompose at 500°C, increasing the content of reactive SiO2 and Al2O3, which participate in secondary hydration reactions with calcium hydroxide (CH). This process forms additional calcium silicate hydrate (C-S-H) gel, ettringite (AFT) crystals, and afwillite, enhancing the concrete microstructure. Notably, coal gangue concrete calcined at 800°C exhibited a porosity of 1.29 % and a compressive strength of 38 MPa after 28 days of curing, meeting the C30 concrete standard. Furthermore, the correlation between the compressive strength of CCGC and its microstructure exceeded 0.72, indicating that fractal dimension analysis is an effective method for predicting concrete strength.